Bromodomain Inhibition Attenuates the Progression and Sensitizes the Chemosensitivity of Osteosarcoma by Repressing GP130/STAT3 Signaling - Jiang, Yafei; Wang, Gangyang; Mu, Haoran; Ma, Xiaojun; Wang, Zhuoying; Lv, Yu; Zhang, Tao; Xu, Jing; Wang, Jinzeng; Li, Yunqi; Han, Jing; Yang, Mengkai; et al. (Frontiers in Oncology, 2021)
Osteosarcoma is the most common primary malignant bone tumor, and there are few ideal clinically available drugs. The bromodomain and extraterminal domain (BET) protein is an emerging target for aggressive cancer and has been confirmed as an attractive target in osteosarcoma, but therapies targeting the BET in osteosarcoma have been unsuccessful in clinical trials to date, and further exploration of specific BET inhibitors is of great significance. In our study, we demonstrated that NHWD-870, a potent BET inhibitor in a phase I clinical trial, significantly inhibited tumor proliferation and promoted cell apoptosis by reversing the oncogenic signature in osteosarcoma. More importantly, we identified NHWD-870 impeded binding of BRD4 to the promoter of GP130 leading to diminished activation of JAK/STAT3 signaling pathway. Furthermore, GP130 knockdown significantly sensitizes the chemosensitivity in vitro. In OS cell-derived xenografts, NHWD-870 effectively inhibited the growth of osteosarcoma. Beyond that, NHWD-870 effectively inhibited the differentiation and maturation of precursor osteoclasts in vitro and attenuated osteoclast-mediated bone loss in vivo. Finally, we confirmed the efficacy of synthetic lethal effects of NHWD-870 and cisplatin in antagonizing osteosarcoma in a preclinical PDX model. Taken together, these findings demonstrate that NHWD-870, as an effective BET inhibitor, may be a potential candidate for osteosarcoma intervention linked to its STAT3 signaling inhibitory activity. In addition, NHWD-870 appears to be a promising therapeutic strategy for bone-associated tumors, as it interferes with the vicious cycle of tumor progression and bone destruction.